Characterization of bismuth oxide catalysts prepared from bismuth trinitrate pentahydrate: influence of bismuth concentration - Ramli, Irmawati; Mhamat Nasudin, Noorfarizan Nasriah; Yap, Taufiq Yun Hin; Abdul Hamid, Sharifah Bee (Elsevier, 2004)
Bi2O3 catalysts have been prepared via precipitation method by using Bi(NO3)3·5H2O as a starting material and NaOH as the precipitating agent. The influence of bismuth concentration on the formation of Bi2O3 nanocrystals was investigated by using XRD, BET, FTIR, SEM and H2-TPR. Low bismuth concentration, resulted in high surface area material with small size crystallite (not, vert, similar36 nm). It also enhanced the oxide reducibility with high reduction activity. XRD patterns of all the samples display pure α-Bi2O3 phase. The SEM images showed the nanostructure of Bi2O3 were non-agglomerated needles.